2011
DOI: 10.1093/protein/gzr028
|View full text |Cite
|
Sign up to set email alerts
|

Engineering highly thermostable xylanase variants using an enhanced combinatorial library method

Abstract: A new directed evolution method was used to enhance the thermostability of the wild-type GH11 xylanase 2 (known as BD-11) from Hypocrea jecorina (Trichoderma reesei). Both Look-Through Mutagenesis (LTM™), which is a method for rapidly screening selected positions in the protein sequence for amino acids that introduce favorable properties, and Combinatorial Beneficial Mutagenesis (CBM™), which is a method for identifying the best ensemble of individual mutations, were employed to enhance the stability of an enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…1062 As discussed above, thermostability may also sometimes (but not always 171173 ) correlate with evolvability, 175 and is the result of multiple mutations each contributing a small amount. 10641069 …”
Section: Enzyme Stability Including Thermostabilitymentioning
confidence: 99%
“…1062 As discussed above, thermostability may also sometimes (but not always 171173 ) correlate with evolvability, 175 and is the result of multiple mutations each contributing a small amount. 10641069 …”
Section: Enzyme Stability Including Thermostabilitymentioning
confidence: 99%
“…30 In some strains, optimal xylanase activity was observed at pH 6.4 and temperature 55°C and xylanase is active up to pH 9 (40.33 IU/ml) and temperature 85°C (48.81 IU/ml) (Agnihotri et al, 2010) 1 and A 27-fold higher production was achieved by cloning and expression (Verma et al, 2011). 89 Recently thermostable xylanase retaining activity at 100 o C for 20 minutes have been found (Hokanson et al, 2011). 35 Bacillus haloduras is a wild (non-genetically manipulated) organism yielding thermo-alkali stable xylanase that acts in submerged fermentation at pH 10.0 (Kumar et al, 2012).…”
Section: Recent Arrivalsmentioning
confidence: 99%
“…89 Recently thermostable xylanase retaining activity at 100 o C for 20 minutes have been found (Hokanson et al, 2011). 35 Bacillus haloduras is a wild (non-genetically manipulated) organism yielding thermo-alkali stable xylanase that acts in submerged fermentation at pH 10.0 (Kumar et al, 2012). 48 To the contrary, thermo-acid stable variants act at pH 2.0 and temperature 80°C (Apel et al, 2008…”
Section: Recent Arrivalsmentioning
confidence: 99%
“…This facilitates the transformation in P. pastoris and subsequent screening and sequencing [21]. It is reported that the combinatorial library method focusing on the amino acids that represent side-chain properties is effective for the directed evolution of smaller-sized enzymes [22]. Since our target protein is relatively large, we selected both error-prone PCR and DNA shuffling in this study.…”
Section: Properties Of Mutant-59 and Mutant-8mentioning
confidence: 99%